Kombinasi Algoritma Huffman dan Algoritma ROT 13 Dalam Pengamanan File Docx - Hendrik Hendrik (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Behind this is often the theft of very important files, where they look for the files they need that they want. With no security for a title or file name, they will be very easy to find the file title they want. With the security of a file that is very important where a lot of people who are not responsible for controlling or owning the file. So this will cause a loss for the file owner if the file is known by others. The huffman algorithm is an algorithm that can be used to compress files, so that the resulting file size becomes smaller than the actual size. Huffman algorithm is a lossless compression algorithm. lossless compression algorithm is a compression technique that does not change an information from the original file. ROT13 (rotate 13) is a encryption substitution cipher that is commonly used in UNIX operating systems. In the ROT13 encryption system a letter is replaced by a letter that is located in the top 13 positions of it. With the existence of an application that implements a combination of the huffman algorithm and the ROT 13 algorithm used in the security of a docx file, making it difficult for file thieves to find the desired file